2019
DOI: 10.1128/aac.00004-19
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Zinc Linolenate, a Selective Antibacterial Agent against Helicobacter pylori

Abstract: Helicobacter pylori is a major global pathogen, and its infection represents a key factor in the etiology of various gastric diseases, including gastritis, peptic ulcers, and gastric carcinoma. The efficacy of current standard treatment for H. pylori infection including two broad-spectrum antibiotics is compromised by toxicity toward the gut microbiota and the development of drug resistance, which will likely only be resolved through novel and selective antibacterial strategies. Here, we synthesized a small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 70 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…The decrease in viability was seen after 48-h exposure to MBC (a 4-log reduction). The next article [65] noted a rapid decrease in the number of viable cells (a total bacterial destruction after 70 min with MIC of zinc linolenate), which was associated with a reduction in intracellular ATP, increase in the permeability of cellular membranes, vesiculation, and spherical forms appearance. In the last analyzed study [43], it was observed that the morphology of H. pylori affected the parameters required to kill the cells of this bacterium.…”
Section: Fatty Acids and Fatty Acid Derivativesmentioning
confidence: 86%
See 3 more Smart Citations
“…The decrease in viability was seen after 48-h exposure to MBC (a 4-log reduction). The next article [65] noted a rapid decrease in the number of viable cells (a total bacterial destruction after 70 min with MIC of zinc linolenate), which was associated with a reduction in intracellular ATP, increase in the permeability of cellular membranes, vesiculation, and spherical forms appearance. In the last analyzed study [43], it was observed that the morphology of H. pylori affected the parameters required to kill the cells of this bacterium.…”
Section: Fatty Acids and Fatty Acid Derivativesmentioning
confidence: 86%
“…In four articles [43,[63][64][65] determining the effect of fatty acids and fatty acid derivatives on H. pylori, one research used microscopy and culture methods demonstrating a bacteriostatic nature of the tested compound [63], while other three studies were expanded to include fluorescent or molecular methods, and here the activity of the compounds was interpreted as bactericidal [43,64,65] ( Table 4 and Figure 4).…”
Section: Fatty Acids and Fatty Acid Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activities against H. pylori , S. aureus , B. subtilis , P. aeruginosa, and K. pneumonia were assayed by examining the MIC using the broth micro-dilution method as previously described [5,35].…”
Section: Methodsmentioning
confidence: 99%